Pengembangan Media Pembelajaran Teka-Teki Silang Sastra Melayu Klasik Berbasis Android - Fina Hiasa; Fitra Youpika; Nafri Yanti (Magister Pendidikan Bahasa dan Sastra Indonesia, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mulawarman, 2022)
This study aims to develop learning media for Indonesian-Malay literary crosswords classical based on android. The android-based crossword puzzle learning media developed with the help of the Proprofs application will be tested on odd semester students taking the History of Literature course, Indonesian Language Education Study Program, FKIP, Bengkulu University. The development of learning media in this study used the Research and Development (R&D) method, where researchers collected research data using a questionnaire based on the Likert scale. This study has three questionnaires: a material expert questionnaire, a media expert questionnaire, and a user response questionnaire of 34 students. As a result, the total score obtained from the combined validation of material experts, media, and users was 139.5, or an average score of 4.1. These results indicate that the learning media of classical Indonesian-Malay literary crosswords that the researcher developed is appropriate for learning activities in the History of Literature course.